Osimertinib – effective treatment of NSCLC with activating EGFR mutations after progression on EGFR tyrosine kinase inhibitors - Skrzypski, Marcin; Szymanowska-Narloch, Amelia; Dziadziuszko, Rafał (Contemporary Oncology/Współczesna Onkologia, 2017)
Non-small cell lung cancer (NSCLC) driven by activating mutations in epidermal growth factor receptor (EGFR) constitutes up to 10% of NSCLC cases. According to the NCCN recommendations, all patients (with the exception of smoking patients with squamous cell lung cancer) should be screened for the presence of activating EGFR mutations, i.e. deletion in exon 19 or point mutation L858R in exon 21, in order to select the group that benefits from EGFR tyrosine kinase inhibitors (EGFR TKIs) treatment. Among approved agents there are the 1st generation reversible EGFR TKIs, erlotinib and gefitinib, and the 2nd generation irreversible EGFR TKI, afatinib. The objective response rates to these drugs in randomised clinical trials were in the range of 56–74%, and median time to progression 9–13 months. The most common determinant of resistance to these drugs is the clonal expansion of cancer cells with T790M mutation (Thr790Met) in exon 20 of EGFR. Osimertinib (Tagrisso™), a 3rd generation, irreversible EGFR tyrosine kinase inhibitor, constitutes a novel, highly efficacious treatment for NSCLC patients progressing on EGFR TKIs with T790M mutation confirmed as the resistance mechanism. Resistance mutation can be determined in tissue or liquid biopsy obtained after progression on EGFR TKIs. Osimertinib has a favourable toxicity profile, with mild rash and diarrhoea being the most common. In this article, we present three cases that were successfully treated with osimertinib after progression on 1st and 2nd generation EGFR TKIs.